Structural and physical analysis of underwater silk from housing nest composites of a tropical chironomid midge - Thorat, Leena; Joseph, Emmanuel; Nisal, Anuya; Shukla, Ekta; RaviKumar, Ameeta; Nath, Bimalendu B. (International Journal of Biological Macromolecules, 2020)
Chironomids are an abundant group of aquatic silk spinning insects. They offer a unique opportunity of silk harvestation without killing them; however, they remained underappreciated models in silk research. Here, we investigate the structural and biomechanical characteristics of silk from the midge, Chironomus ramosus. A combination of microscopic (SEM), spectroscopic (CD and IR), structural (XRD), thermal (DSC and TGA) and mechanical measurement tools and techniques were employed to gain critical insights on midge silk. Maximum yield of silk was obtained from Chironomus in similar to 2.5 h, the shortest time reported among insects. The network of water-insoluble silk fibres possessed the smallest diameter of 110 +/- 35 nm, known for any insect silk, qualifying its superiority in fibre fineness. We demonstrate a cruelty-free silk extraction method in contrast to the conventional violent techniques. Structural characterization indicated coexistence of various secondary conformations, beta sheets being predominant. We compare and contrast these features to well-characterized caddisfly and silk-worm silks and highlight the uniqueness in midge silk that render mechanical stability and potentially contribute to its multi-functionalization. We thus propose Chironomus as an emerging candidate of water-borne silk, especially in the context of the `Peace silk' industry, aiming to develop non-violent methods for silk harvestation from animals. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chironomus; Commercial applications; Housing nest composite; Peace silk; Underwater silk